ANALISIS FAKTOR KEBERHASILAN PERANGKAT LUNAK LIVIN BY MANDIRI PADA PT BANK MANDIRI - Utami, Vita Dwi; Elfanza, Vellyn Chalista; Kusuma, Rahayu Linda; Albana, Ilham (Jurnal Ilmiah Sistem Informasi, 2024)
In the modern era like now, many human needs can be met with a supporting technology. This is because of a demand of circumstances and needs. One form of meeting technological needs by humans is software in the banking sector. Supporting technology used in a banking includes software that is designed simply with the hope that users will be able to understand the use of the software. This refers to the assessment of success factors in a software in a company where its function is considered very important in various aspects. As in the company PT. Bank Mandiri (Persero). Tbk which until now has mobile banking software that is widely used or accessed by users. This research took place at Bank Mandiri Banyumas KC Purwokerto. Software that is already available then requires management actions for processes in a project. Livin by Mandiri is one of the software applications that are in great demand by users/customers. To test success by using statistical validity tests using materials / results from questionnaires and interviews to later measure how many customers / users use the Livin by Mandiri application. The target used as data collection material is 5 people with specific application users. From the results of the validity test calculation, it will be seen that the calculation is valid and not